Prevalence of Feline Scabies at Puskeswan Bangsalsari, Jember During 2021-2023 - Rifky Nugroho; Epy M. Luqman; Tri Wahyu Suprayogi; Suharti Aryanata; Suhita Aryaloka; Aswin Rafif Khairullah (Universitas Airlangga, 2025)
Feline Scabies is a highly contagious and zoonotic skin disease. It can be transmitted from animals to humans and from person to person. This research was carried out at Puskeswan Bangsalsari, Jember, East Java. Data were collected regarding the number of patients from 2021 to 2023 and organized monthly by the occurrence of scabies in cats. The prevalence of feline scabies at Puskeswan Bangsalsari, Jember, in 2021 was 31.29%, based on 133 scabies cases out of 425 total patients. In 2022, the prevalence of feline scabies was 33.21%, based on 186 cases out of 560 total patients. In 2023, the prevalence increased to 38.53%, with 210 cases recorded from a total of 545 patients. The cumulative prevalence of feline scabies at Puskeswan Bangsalsari, Jember, from 2021 to 2023, was 34.74%, based on 529 scabies cases out of a total of 1,520 patients. The highest prevalence of feline scabies was observed in August 2023, reaching 56.71%, with 21 cases out of 37 total patients. This may have been caused by high humidity, which could affect cage hygiene and create favorable conditions for Sarcoptes scabiei to complete its life cycle.